The Effect of the Environmental Learning Model on the Character of Care for the Environment of Class IV Student: Pengaruh Model Environmental Learning Terhadap Karakter Peduli Lingkungan Siswa Kelas IV) - Sayidatus Saniyah; Dr. Akhtim Wahyuni M. Ag (Universitas Muhammadiyah Sidoarjo, 2022)
This research aimed to investigate the effect of implementing the Environmental Learning model on the development of environmental care character among fourth-grade students at SDN Pangkemiri 1. A pre-experimental design using a one-group pretest-posttest method was employed to assess the changes in environmental care character before and after the intervention. The data collection involved administering a questionnaire to the students before and after the implementation of the Environmental Learning model. The results revealed a significant improvement in the average scores of environmental care character from pretest (2.342) to posttest (3.271). The calculated eta square value (0.776) indicated a substantial effect, demonstrating the efficacy of the Environmental Learning model in fostering environmental care character among the fourth-grade students. These findings underscore the importance of incorporating such models into educational practices to promote environmental consciousness and responsible behavior among young learners. Highlights: The Environmental Learning model positively influences the development of environmental care character among fourth-grade students. The pre-experimental design with a one-group pretest-posttest method allows for the evaluation of changes in environmental care character. The findings emphasize the significance of incorporating the Environmental Learning model to foster environmental consciousness and responsible behavior in young learners. Keywords: Environmental Learning, Character Development, Fourth Grade Students, SDN Pangkemiri 1, Quantitative Study.